Development of a sagebrush steppe plant community 33 years after surface disturbance - Bowles, Brock, author; Paschke, Mark, advisor; Brown, Cynthia, committee member; Meiman, Paul J., committee member (Colorado State University. Libraries, 2011)
The sagebrush steppe ecosystem is the most endangered ecosystem in North America due to sagebrush eradication, weed invasions and energy development. Restoration of sagebrush steppe plant communities damaged by these disturbances is extremely important to the survival of endangered or threatened sagebrush dependant species such as the sage-grouse and Columbia Basin pygmy rabbit. In the fall of 1976 a field experiment was initiated in the Piceance Basin of northwestern Colorado to study the effects of six seed mixes and three fertilizer treatments on the restoration of a sagebrush steppe plant community after surface disturbances associated with oil shale development. We revisited these study plots during 2008 and 2009 to determine the long-term effects of these treatments on plant community development. Results from this 33-year study indicate that seed mix has long-term effects on the plant community production and composition. The composition of the plant community in all seeded plots was very similar to that of the seed mix used in 1976. The late-seral dominant shrub species in this system, sagebrush (Artemisia tridentata), which was not seeded in any of the treatments, did not recover as the dominant shrub species. An initial fertilizer treatment had short-term effects on the plant community but its effects have become insignificant over time. A seed mix containing native species with no fertilizer addition appears to be the best long-term treatment for restoring a native sagebrush steppe plant community in this study.
Keywords: seedmix; fertilizer; Piceance; plant community; restoration; sagebrush